FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Rendy, Rendy; Suhendah, Rousilita (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study was to study the effect of liquidity, leverage, and profitability  on  firm  value  in  manufacturing  companies  listed  on  the  Indonesia  Stock Exchange (IDX) in the period 2015-2017. This study used a non-probability sample method with a purposive sampling technique. The number of samples used in this study were 96 samples. The results of this study indicate that liquidity (CR) has a significant and negative effect on firm value, leverage (DAR) does not affect on firm value, and profitability (NPM) has a significant and positive effect on firm value. leverage (DAR), and profitability (NPM) together against company value.